"IMMUNOHISTOCHEMICAL CHARACTERISTICS OF PATIENTS WITH MACRO- AND GIANT NON-FUNCTIONAL PITUITARY ADENOMAS" (World Bulletin of Public Health, 2026)
The aim of the study is to perform a comparative analysis of immunocytochemistry data from groups of patients with macro- and giant non-functional pituitary adenomas. (NFPA)
Keywords: NFPA; IHC; proliferation markers